Managing - Mintzberg, Henry (UK Prentice Hall, 2011)
Contents include: 'Managing Ahead', 'The Dynamics of Managing', 'A Model of Managing', 'The Untold Varieties of Managing' and 'Managing Effectively'.
Age Group: Adult
Keywords: Business; Leadership; Nonfiction; Management; (UGB261) Management Thought